2008
DOI: 10.1007/s10389-007-0176-3
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk behaviour, knowledge and attitude related to HIV transmission: a study among a migrant tribal group living in the slums of Bhubaneswar City, Orissa, India

Abstract: Objectives The purpose was to identify the risky sexual behaviour, knowledge and attitude related to HIV transmission among migrant tribals living in the slums of a state headquarters city in India. Methods From four Santal tribe-dominated slums in Bhubaneswar City, Orissa, India, a sample of 113 respondents 15-40 years of age was recruited. Both quantitative and qualitative data were obtained through semi-structured interviews.Results In this migrant tribal community, the majority of women are sexually active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Delivery of child occurs at home under unhygienic conditions without medical help or nursing. Common factors like malnutrition, poor hygiene, lack of education, low economic status, unawareness and absence of modern medical facility make tribal people most vulnerable to several chronic and infectious diseases such as sexually transmitted diseases and cancer [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Delivery of child occurs at home under unhygienic conditions without medical help or nursing. Common factors like malnutrition, poor hygiene, lack of education, low economic status, unawareness and absence of modern medical facility make tribal people most vulnerable to several chronic and infectious diseases such as sexually transmitted diseases and cancer [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although India's tribal populations are at considerable risk of STIs because of their relatively open sexual mores compared to traditional Indian society (14,15), limited attention has been paid to HIV among them. Previous studies have documented high rates of STIs, limited prevention and surveillance, low awareness, and widespread misconceptions about HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented high rates of STIs, limited prevention and surveillance, low awareness, and widespread misconceptions about HIV. These factors, combined with inadequate healthcare, create a fragile situation susceptible to the rapid spread of HIV in most tribal areas (10,14,15). While it could be expected that HIV-related stigma would also be high, the NFHS-3 data did not show large variations between tribal and non-tribal respondents in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…Childbirth generally occurs at home without proper medical interventions. Other common factors like malnutrition, lack of education, low economic status, unawareness, and absence of modern medical facilities make tribal people most vulnerable to several chronic and infectious diseases such as sexually transmitted diseases 10,11 . A recent study from our laboratory also indicated a higher incidence of infectious diseases and lower incidence of chronic diseases among the tribal communities in West Bengal, India 12 …”
Section: Introductionmentioning
confidence: 65%